Pragmatics and Discourse Analysis: The Properties of Everyday Language Found in “From South Sumatera to Ohio, Indiana, & Utah” - Badriyah Ulfah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
Analyzing everyday language properties is crucial for uncovering the nuanced layers of meaning within literary works. Therefore, this study explores Prof. Diemroh Ihsan's book, From South Sumatera to Ohio, Indiana, and Utah, through the lens of pragmatics and discourse analysis, focusing on everyday language properties as outlined in Grundy's (2008) framework. Specifically, the study examines indirect meanings, cultural contexts, and inferences present in the narrative. The qualitative descriptive technique was chosen for its suitability in systematically capturing and interpreting descriptive data, such as written words in the book, allowing for a detailed exploration of linguistic nuances within the text. This approach enables an in-depth understanding of how language operates within cultural and contextual dimensions of the narrative. The analysis reveals eight instances of implicit meaning, nine cultural contexts, and one inference, illustrating the intricate dynamics between language and culture. By acting as a cultural bridge that portrays diverse culinary traditions, festive celebrations, and economic perspectives, this study highlights the interplay between language and cultural interpretation. The findings lay a foundation for future cross-cultural analyses, contributing to a deeper understanding of how language and culture intersect in literary works.Everyday Language Properties